The SAGE encyclopedia of the sociology of religion. 2 - Possamai, Adam; Blasi, Anthony J. (Los Angeles, CA : SAGE Publications, Inc., 2020)
The SAGE Encyclopedia of the Sociology of Religion takes a three-pronged look at this, namely investigating the role of religion in society; unpacking and evaluating the significance of religion in and on human history; and tracing and outlining the social forces and influences that shape religion. This encyclopedia covers a range of themes from: fundamental topics like definitions secularization dimensions of religiosity to such emerging issues as civil religion new religious movements This Encyclopedia also addresses contemporary dilemmas such as fundamentalism and extremism and the role of gender in religion.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Religion and sociology -- Encyclopedias; Fundamentalism -- Encyclopedias